2021
DOI: 10.1007/s12264-021-00770-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of CDH11 with Autism Spectrum Disorder Revealed by Matched-gene Co-expression Analysis and Mouse Behavioral Studies

Abstract: A large number of putative risk genes for autism spectrum disorder (ASD) have been reported. The functions of most of these susceptibility genes in developing brains remain unknown, and causal relationships between their variation and autism traits have not been established. The aim of this study was to predict putative risk genes at the whole-genome level based on the analysis of gene co-expression with a group of high-confidence ASD risk genes (hcASDs). The results showed that three gene features – gene size… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Subsequent research discovered altered CDH11 expression in individuals with ASD, further suggesting that changes in its expression may partially contribute to the pathological process of ASD. In line with this, behavioral studies conducted on mice with CDH11 deficiency revealed a range of autism-like behavioral changes [ 91 ], providing further confirmation of the significance of CDH11 in ASD.…”
Section: Autism Spectrum Disordermentioning
confidence: 54%
See 2 more Smart Citations
“…Subsequent research discovered altered CDH11 expression in individuals with ASD, further suggesting that changes in its expression may partially contribute to the pathological process of ASD. In line with this, behavioral studies conducted on mice with CDH11 deficiency revealed a range of autism-like behavioral changes [ 91 ], providing further confirmation of the significance of CDH11 in ASD.…”
Section: Autism Spectrum Disordermentioning
confidence: 54%
“…To date, a total of 7 molecularly confirmed cdh11 -related cases of EWS have been reported, originating from 5 families, including two sisters from a consanguineous couple, a male child, an Indian female, a sibling pair, and a male individual from Japan. Homozygous variants in cdh11 were identified in these patients, confirming EWS as an autosomal recessive disorder, wherein one of its causal factors is attributed to loss-of-function variants in cdh11 [ [91] , [92] , [93] , [94] ]. However, it is important to emphasize that the current understanding of cdh11 in relation to this syndrome remains limited, necessitating further validation of its reliability.…”
Section: Elsahywaters Syndromementioning
confidence: 80%
See 1 more Smart Citation
“…Heterozygous Arid1b knockout (hKO) mice exhibit ASD-like traits associated with social behavior, anxiety, and persistence, as well as weight loss, impaired motor coordination, and hydrocephalus (Shibutani et al, 2017 ). Chd11 -null mice, but not Chd9 -null mice, have multiple autism-like behavioral changes (Wu N. et al, 2021 ). The small or missing regions of the anterior commissure of Tbr1 +/– mice lead to defective neuronal differentiation in the amygdala, which may serve as a suitable model for determining how autism genes control neuronal circuits, neural activity, and behaviors (Huang et al, 2019 ).…”
Section: Vertebrate Models Of Asd-related Syndromesmentioning
confidence: 99%
“…Although the exact etiology of ASD remains an enigma, at least 30% of cases have an underlying genetic etiology [28][29][30][31][32][33][34][35]. The most common gene variants involved in ASD include SHANK3, MECP2, NLGN3, NRXN1 and FMR1 [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], some of which are regulated by the metabotropic glutamate receptor (mGluR) pathway, especially mGluR5, thus making it a very attractive target for understanding the pathogenesis of ASD [51].…”
Section: Introductionmentioning
confidence: 99%